Middle-aged same-sex attracted women and the social practice of drinking. Issue 5 (20th October 2019) - MacLean, Sarah; Savic, Michael; Pennay, Amy; Dwyer, Robyn; Stanesby, Oliver; Wilkinson, Claire
ABSTRACT: As a group, middle-aged same-sex attracted women (SSAW) appear to consume more alcohol than exclusively heterosexual women in the same age range; however, few studies document their collective drinking practices or identify opportunities to reduce associated harms. Online surveys which included open-ended questions were completed by a self-selected sample of SSAW ( N = 134) aged 36–51, recruited in Victoria, Australia. We identify 12 sub-elements of SSAW's collective drinking practice using a schema grounded in social practice theory (SPT). Responses are compared for SSAW who consumed alcohol with others at moderate and at heavier levels, based on screening. Heavier drinking respondents were more likely to observe that: alcohol use is normalised for SSAW; they are not pressured to drink; drinking produces pleasurable effects; drinking facilitates management of uncomfortable moods and that venues welcoming SSAW are saturated with alcohol. In line with SPT, links between sub-elements described by heavier drinkers are explored to identify potential interventions. For example, we recommend an expansion of social opportunities without alcohol that engender affirming affective states for SSAW. Further, many SSAW's commitment to the importance of moderation and rejecting coercion to drink could be used to combat the conviction that drinking is an inevitable response to discrimination experienced by sexual minorities. It was apparent that although they drank with other SSAW, our survey respondents did not share a consistent or altogether unique drinking culture. We suggest that an SPT approach entailing data coding to multiple sub-elements supports the identification of diverse configurations of drinking practice within heterogeneous subpopulations.